MENINGKATKAN EFEKTIFITAS DALAM TEXT PREPROCESSING DENGAN IMPLEMENTASI ELECTRONIC DATA PROCESSING PADA TEKS BERITA - Rafdi Reyhan Zhafari (2023)
The rapid and massive dissemination of information certainly requires fast and massive processing as well. Over time, technology has become a complicated matter to filter or abstract from the initial data, this is what makes electronic data processing a thing that humans accidentally or intentionally have to adapt so they are not left behind from getting the information they need. In this research, electronic data processing was carried out on text processing using news text. In the study, a comparison was made using other devices, where with the device in the study, the result was 18.917 seconds at the preprocessing stage, while the results for the colab research device were 17.431 seconds